(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda pays utmost importance to Agni as it is the inherent factor behind every change that occurs in the body. The persistent Alpagni is said to be the causative factor for all the diseases. This is why Ama pachana and Agni deepana became the basic line of treatment in many diseases. Detailed and in-depth analysis of various classical references and articles published in reliable web resources has been done on the topic Deepana and Pachana and got some inferences. Pacana has role in conditions of Ama while Deepana in Agnimandya. But in our day to day practice when we have different Oushadha yoga, we can’t discriminate it in the formulations. The range of Deepana and Pachana may vary in each formulation. We may say at the Koshta level Deepana karma improves the Abhyavaharana shakti by stimulating the appetite and Pachana karma improves the Jaranashakthi by improving the digestion.